Starting a small business in Jamaica: a guide - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The document explains that the feasibility study will determine how certain important factors will affect the possible and success of the business, and will help the persons with the 'idea' to decide whether it is worth going a head with or not. The method they will use for doing a simple feasibility study has four parts: 1) examining the aptitudes and capabilities for running the business they are thinking about starting; 2) estimating the probable market for the product(s) or service(s) they propose to offer; 3) determining the probable cost of their product(s) or service(s); 4) analyzing the probable income they would receive from the business in comparison with their expectations and with the return for other alternative uses of their time and skills. The guide finishes with the observation that no one can predict for anyone whether or not his business will start of well and continue growing. The feasibility study, therefore, is meant to make someone aware of some aspects of running a business which he had given some thought, but needed to lock at again in more detail.